RETRACTED: Career anchors and value orientations as tools for evaluating soft skills of technical university students in the context of digital socialization - Kuren Sergey; Beluzhenko Olga; Demyanov Alexey; Dontsov Nikolay; Kosenko Evgeny (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001